2016
DOI: 10.4209/aaqr.2015.07.0455
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis, Transportation Mode of Atmospheric Mercury and Criteria Air Pollutants, with Meteorological Parameters at Two Remote Sites of Mountain and Offshore Island in Asia

Abstract: This study presents a comparison of trace (Hg) and criteria (CO, SO 2 , NO x , O 3 and PM 10 ) air pollutants monitored at two remote sites with the same latitude but different altitude: Mt. Lulin and the Penghu Islands, in Taiwan from 2011 to 2012. A filtering technique was comprehensively applied to distinguish the climatic characteristics of the two remote sites, as well as to determine their discriminant factor. The concentrations of air pollutants monitored at Mt. Lulin were generally lower than those at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Furthermore, adding radon measurements as an additional trace gas proxy of atmospheric transport and mixing processes, Chamber et al (2016) demonstrated an improved method for representing trans-boundary transport of anthropogenic pollution in East Asia. Chen et al (2016) also presented correlation analyses of total gaseous mercury and the aforementioned trace gas pollutants (including PMs) to distinguish the climatic characteristics (e.g., scenario vs. background mercury) of the measurements and to determine their discriminating factors.…”
Section: Atmospheric Compositionmentioning
confidence: 99%
“…Furthermore, adding radon measurements as an additional trace gas proxy of atmospheric transport and mixing processes, Chamber et al (2016) demonstrated an improved method for representing trans-boundary transport of anthropogenic pollution in East Asia. Chen et al (2016) also presented correlation analyses of total gaseous mercury and the aforementioned trace gas pollutants (including PMs) to distinguish the climatic characteristics (e.g., scenario vs. background mercury) of the measurements and to determine their discriminating factors.…”
Section: Atmospheric Compositionmentioning
confidence: 99%
“…Mercury (Hg) and its compounds emitted from anthropogenic sources, e.g., coal-fired power plants, industrial boilers, waste incinerators, sinters, and cement plants, have tempted substantial attention due to their high toxicity, bioaccumulability, and global transport behaviors in atmosphere (Kumari et al, 2015;Chen et al, 2016;Marusczak et al, 2016;Wang et al, 2016). Coal-fired power plants were reported as the largest single source in most countries in Hg emissions (Pacyna et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mercury (Hg) is a worldwide environmental contaminant that leads to the contamination of forest, soil, water, plants, snow, and others [1]. It is well accepted that elemental Hg (Hg 0 ) can travel long distances in the atmosphere, impacting aquatic systems in remote regions through deposition [2,3,4,5,6]. Consequently, atmospheric deposition is regarded as the principal source of Hg input for remote pristine regions with rare anthropogenic Hg sources [7].…”
Section: Introductionmentioning
confidence: 99%